Non-destructive testing (NDT) in industry 4.0: a brief review - Sophian, Ali (Institute for Research and Community Services, 2020)
The fourth industry revolution, or IR 4.0, has seeped into the national policy of governments all around the world, thanks to its perceived importance and relevance for both economic growth and sustainable development. With the advancement of internet connectivity, big data and cloud computing, IR 4.0 has promised fresh improvement and innovation to bring the automation of the manufacturing industry to a new level. It is also believed that the technologies supporting IR 4.0 will also enhance non-destructive testing (NDT) in many ways, which, in turn, will lead to increased product quality, better safety and improved sustainability. This presentation will highlight the state-of-the-art research on this subject and discuss how it will project into the future.